Production of minor ginsenosides by combining Stereum hirsutum and cellulase. - Wenhua Yang (Public Library of Science (PLoS), 2021)
Minor ginsenosides (MGs) (include ginsenoside F2, Compound K, PPT, etc), which are generally not produced by ginseng plants naturally, are obtained by deglycosylation of major ginsenosides. However, the conventional processes used to produce deglycosylated ginsenosides focus on the use of intestinal microorganisms for transformation. In this study, an edible and medicinal mushroom Stereum hirsutum JE0512 was screened from 161 β-glucosidase-producing soil microorganisms sourced from wild ginseng using the plate coloration method. Furthermore, JE0512 was used for the production of CK from ginseng extracts (GE) in solid-state fermentation (SSF) using 20 g corn bran as substrate, 4 g GE, and 20% inoculation volume, and the results showed that the highest CK content was 29.13 mg/g. After combining S. hirsutum JE0512 with cellulase (Aspergillus niger), the MGs (F2, CK, and PPT) content increased from 1.66 to 130.79 mg/g in the final products. Our results indicate that the Stereum genus has the potential to biotransform GE into CK and the combination of S. hirsutum JE0512 and cellulase could pave the way for the production of MGs from GE.